Tonga : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on Tonga's 2013 Article IV Consultation discusses the economic development and policies. Banks in Tonga have been fixing their balance sheets since late 2008. Shrinking the loan books and increasing holdings of reserve assets have prompted negative macro-financial linkages, and reduced business confidence. In response, the National Reserve Bank of Tonga has aggressively infused liquidity into the system, and stepped up risk-based supervision. Progress in improving the regulatory and institutional infrastructure has also continued, including inauguration of a credit bureau. Major gains have been made in budget transparency, the establishment of a Treasury Single Account system, and better prioritization of the budget.